If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2p + 4q = 32 Solving 2p + 4q = 32 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-4q' to each side of the equation. 2p + 4q + -4q = 32 + -4q Combine like terms: 4q + -4q = 0 2p + 0 = 32 + -4q 2p = 32 + -4q Divide each side by '2'. p = 16 + -2q Simplifying p = 16 + -2q
| -35+7x=-5(4-2x) | | -9.6=2.4 | | 7(y-9)=2(3y+2)-67 | | 3x+11=11x+1 | | 4+a/3=1 | | 3x+4+4x=39 | | 8ax-7a=19a-5ax | | 3m-6=5w-2(w-2) | | 3(m+5)=33 | | 12x-8=3x-3 | | -5k+6(k-2)=-2k-12 | | 4x^2+24x+5=0 | | e(10)=2n | | -14n+q=n+-4n | | 8-(v+3)=5v-5 | | x+xy+y=30 | | 3a-7a=-5a+8 | | 4+4x=8+2x | | 4x-20=-8 | | 3x(x-5)=(7x)(7x)-16x | | 3(3x-1)=-7x-8 | | X+3x+x+x=1000 | | 10-10x=36-24x | | y^2-6y+16x+9=0 | | 13x-15=6x+8 | | 3x^2+8x-1=3 | | 3(4k+14)=10k+(-2k)+(-14) | | 6xy+10x-3y=40 | | k/13=-16 | | 13x+9=5x-8 | | k=-16 | | [x]=1 |